A long way down [large type] - Silvis, Randall, 1950- (Silvis, Randall, 1950- Ryan DeMarco mystery, 2019)
"Ryan DeMarco is returning to Erie, Pennsylvania after his estranged wife attempts suicide and beginning an investigation into three recent murders in a nearby town that may be related to a cold case dating back to DeMarco's high school days."--Publisher.